Roman Pollak i jego perspektywa nauki w II Rzeczypospolitej - Jeszke, Jaromir (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The article presents an analysis of the views on science held by Roman Pollak, a prominent literary historian of the interwar period. The source material consists of Pollak’s texts published in “Nauka Polska. Jej potrzeby, organizacja i rozwój” (Polish science. Its needs, organisation and development) issued by the Józef Mianowski Fund and his longer article Nauka na Powszechnej Wystawie Krajowej (Science at the Polish General Exhibition) written around the inauguration of the Polish General Exhibition in Poznan in 1929. The article presents a portrait of a scholar who strongly emphasised the role of creative processes in science, was significantly influenced by the centralising reforms of science in Italy in the interwar period and who projected a vision of the humanities focused on synthetic analyses serving as the core of studies in a given area.